Management and survival rates for malignant pleural effusions at Tishreen University Hospital - الجندلي , اسماعيل; قنجراوي, أكثم; سعد, أحمد (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Cholelithiasis is acommon and dangeros healthy matter, so thatThe time interval between endoscopic retrograde cholangiopancreatography (ERCP) and laparoscopic cholecystectomy (LC) is a matter of debate. This study was planned to compare early LC versus late LC. Aim of study: Evaluation of the optimal time for laparoscopic cholecystectomy after a procedure ERCP by studying the results and complications of early and late cholecystectomy Patients and Methods:This is a prospective randomized study on patients who are presented with concomitant gallbladder and common bile duct stone. The study population was divided into two groups; group (A) managed by early LC within three days after ERCP; and group (B) managed by late LC after 72hours after ERCP. Results: There was no significant difference in demographic and laboratory findings in both groups. Group A patients had significantly shorter hospital stay and less operative difficulty. The duration of surgery was significantly low in group A. There was no significant difference in rate of conversion to open cholecystectomy. Conclusion: Early LC post-ERCP is associated with short hospital stay and duration of surgery and less operative difficulty and complications. Therefore, we recommend that LC can be safely performed within 72 hours after ERCP.